Development strategy of pumped storage in underground space of closed/abandoned mines - Yang Ke; Fu Qiang; Yuan Liang; Chen Ning; Liu Qinjie; Yang Qinggan (矿业科学学报, 2023)
To achieve carbon peaking and carbon neutrality, China has deepened its energy revolution with the largest renewable energy power generation capacity in the world.In face of the unstable power supply of large-scale renewable energy, a new power system has been proposed and constantly upgraded, which promoted the construction and development of pumped storage power station.Under terrain constraints and the ecological red line, the site selection of traditional pumped storage power station is a hard nut to crack.At the same time, a large number of closed/abandoned mines and resource exhausted cities emerged in the process of coal capacity reduction.This study gave a detailed overview of the status quo of pumped storage power station in China, and analyzed the environmental benefits of the combination of closed/abandoned mines and pumped storage, such as water resource pressure relief and greenhouse gas emission reduction.Based on the different modes of closed/abandoned mine pumped storage power stations, this study analyzed the application potential of closed/abandoned mine pumped storage.Finally, this paper proposed the development strategy of China's abandoned mine pumped storage, and the prospects of closed/abandoned mine+energy storage in multiple industries.